Transformasi Gerakan Radikalisme Menuju Moderasi Beragama - Fatmawati Hilal, Fatmawati (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2023)
This study discusses the process by which a radicalism movement undergoes a transition into a movement promoting religious moderation. The analysis employs qualitative research methodologies, including literature studies and field research. Radicalism movements frequently exhibit severe manifestations in religious practices and possess the capacity to incite significant societal conflicts. Consequently, the transformation of radical movements into moderate movements assumes paramount significance in fostering a climate of harmony and religious tolerance. This study highlights the significance of religious organizations, educational institutions, and social variables in the process of transforming radicalism movements into movements promoting religious moderation. Further exploration is warranted on the contemporary understanding of religion, the promotion of open inter-religious dialogue, the implementation of inclusive education for fostering understanding, and the initiatives aimed at empowering communities. The findings mentioned above possess the potential to serve as a foundation for policymakers and religious practitioners in formulating efficacious measures aimed at preventing and addressing the phenomenon of radicalization toward religious moderation. Several obstacles are encountered in this context, including disseminating radical ideology, addressing social and economic needs, combating isolation and online extremism, the scarcity of moderate leaders, limiting law enforcement and security measures, promoting inter-religious dialogue and education, and enhancing public awareness. By comprehending this process of transition, it is anticipated that strategies can be formulated to prioritize inter-religious dialogue, inclusive religious education, and community empowerment, thus mitigating the likelihood of conflict and fostering harmonious relations across religious communities.